Managing employee performance problems - Tompkins, Neville C. (Crisp Pub. Menlo ParkUS, 1997)
Provides help for staff managers who face deterioration of job performance by employees. Examines responsibilities both of managers and of employees, and suggests ways of improving the quality of the workforce. Provides fact sheets on 29 specific problem situations including, insubordination, anger, sexual harssment, and persons with disabilities. Gives guidance on modifying performance.